2022
DOI: 10.3390/nano12030448
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Dry Printing for SERS and Photoluminescence-Active Gold Nanostructures Preparation for Detection of Traces in Dye Mixtures

Abstract: We proposed a novel method of nanostructure preparation for observation of surface-enhanced Raman spectroscopy (SERS) and metal-enhanced fluorescence (MEF) based on the deposition of gold nanoparticles (GNPs) above the thin dye film by dry aerosol printing. We detected various enhanced SERS and MEF signals of films of malachite green (MG) and rhodamine B (RhB) mixtures, depending on the surface packing density of Au NPs on the strip, and found the optimum one to achieve the 3.5 × 105 SERS enhancement. It was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…[238,264,265] It has better resolution, can avoid the coffeering effect, and can use a wider range of materials and deposition rates, but the AJP system is costly and requires more maintenance than inkjet. Its application is reported in manufacturing various sensors, [266][267][268][269][270] electronic components, [271][272][273][274][275] electronic circuits' micro-electrical connections, [245,276,277] and mmwave circuits. [278] There is no reported usage of AJP in the manufacturing of rectenna, except for one report of a passive RFID tag.…”
Section: Aerosol Jet Printingmentioning
confidence: 99%
“…[238,264,265] It has better resolution, can avoid the coffeering effect, and can use a wider range of materials and deposition rates, but the AJP system is costly and requires more maintenance than inkjet. Its application is reported in manufacturing various sensors, [266][267][268][269][270] electronic components, [271][272][273][274][275] electronic circuits' micro-electrical connections, [245,276,277] and mmwave circuits. [278] There is no reported usage of AJP in the manufacturing of rectenna, except for one report of a passive RFID tag.…”
Section: Aerosol Jet Printingmentioning
confidence: 99%
“…It was also revealed that the good uniformity of micro-ring structures led to higher improvement, while an exposed gold layer caused a reduction in the height and an expansion of the spectral absorbance. It is conceivable that the enhanced spectral absorbance can be controlled by the gold micro-ring structures on a quartz glass plate [23,24]. The optical characteristics of the gold layer on a glass plate were assessed via extinction spectrum.…”
Section: The Spectral Absorbance Propertiesmentioning
confidence: 99%
“…There are many ways to produce and deposit NPs, among which we will focus on the so-called aerosol techniques, which result in the formation of particles dispersed in a gaseous medium [8,9]. Aerosol-based NP generation methods can be combined with direct deposition methods, such as collection on filters [10], impaction printing [11,12], thermophoretic- [3,13], or electric field-guided deposition [14,15], hence providing powerful tools to fabricate nanoparticle films for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…Since spark ablation can conveniently be used to produce multielement NPs by simply combining dissimilar alloyed or 2 of 16 compacted electrodes [34,35], this tunability even includes the crystal structure of the produced particles [29,36,37]. NPs generated via spark ablation have been successfully used in various applications, such as gas- [4,[38][39][40][41][42][43] and light [44] sensors, catalytic surfaces [45,46], or SERS substrates [10,12,[47][48][49][50]. These applications used different approaches to deposit the NPs to a surface, starting from the most straightforward filtering [10] to a highly sophisticated, electrical field-assisted 3D microprinting method [49].…”
Section: Introductionmentioning
confidence: 99%